Family type and family size as correlates of parents’/guardians’ disposition towards girl-child education in Tertiary Institutions in Delta State, Nigeria - Igbineweka, Martins Noyosase; Omoragbon, Ebuwa; Omamuli-Igbinoba, Okeoghene O. (Insight: Jurnal Ilmiah Psikologi, 2023)
The study investigated Family type and Family size as correlates of parents'/guardians' disposition towards girl-child education amongst female students in public tertiary institutions in Delta state, Nigeria. Two research aims, with their corresponding advantages were raised and tested at 0.05 alpha levels. Correlational survey design was used with a population was ten thousand five hundred and thirty-six (10,536) female students from three (3) public tertiary institutions, with a sample of 250 female students. The multistage sampling technique was adopted and a questionnaire titled "Family Types, Family size and Socioeconomic Status Questionnaire" (FTFTSSQ) adapted from Ofuani (2013), was used as the instrument and it consisted of three sections, A, B and C, with reliability coefficient of .88. The hypothesis was analysed using linear regression. The results indicated that Family type significantly predicts parents’/guardians’ disposition towards girl-child education. However, family size, does not significantly predict parents’/guardians’ disposition towards girl-child education in tertiary institutions in Delta State. It was concluded that Family type significantly predicts parents’/guardians’ disposition towards girl-child education; while, family size does not significantly predict parents’/guardians’ disposition towards girl-child education. Among the recommendations was that smaller family be encouraged, such as monogamy so as to allow the flow of scarce resources in pursuing the girl-child education in tertiary institutions and also, there was need for smaller family size, as larger family size was perceived to negate a child's outcomes due to scarce resources